Family Medical Care : A Four-Volume Illustrated Series Covering All Aspects of Health Care (Volume 2) - Knight, John F. (Australia Signs Publishing Company, 1984)
This chapter will examine the current actions, including lifestyle measures, for the prevention and management of non-communicable diseases within a South African context. It will also focus on the biological, behavioural and social determinants of health. Interventions and initiatives directed at primary, secondary and tertiary prevention of chronic non-communicable diseases are also discussed. This chapter ends with recommended lifestyle changes, which can be taken to influence the adoption of healthy lifestyles, and therefore reduce the risks for chronic non-communicable diseases.
Include Ilustrations
Keywords: Medicine, Popular -- Health